Diagnostic accuracy of prehospital triage tools for identifying major trauma in elderly injured patients: A systematic review. Issue 2 (February 2021) - Fuller, Gordon; Pandor, Abdullah; Essat, Munira; Sabir, Lisa; Buckley-Woods, Helen; Chatha, Hridesh; Holt, Chris; Keating, Samuel; Turner, Janette
Abstract : BACKGROUND: Older adults with major trauma are frequently undertriaged, increasing the risk of preventable morbidity and mortality. The aim of this systematic review was to evaluate the diagnostic performance of prehospital triage tools to identify suspected elderly trauma patients in need of specialized trauma care. METHODS: Several electronic databases (including MEDLINE, EMBASE, and the Cochrane Library) were searched from inception to February 2019. Prospective or retrospective diagnostic studies were eligible if they examined prehospital triage tools as index tests (either scored theoretically using observed patient variables or evaluated according to actual paramedic transport decisions) compared with a reference standard for major trauma in elderly adults who require transport by paramedics following injury. Selection of studies, data extraction, and risk of bias assessments using the Quality Assessment of Diagnostic Accuracy Studies-2 (QUADAS-2) tool were undertaken independently by at least two reviewers. Narrative synthesis was used to summarize the findings. RESULTS: Fifteen studies met the inclusion criteria, with 11 studies examining theoretical accuracy, three evaluating real-life transport decisions, and one assessing both (of 21 individual index tests). Estimates for sensitivity and specificity were highly variable with sensitivity estimates ranging from 19.8% to 95.5% and 57.7% to 83.3% for theoretical accuracy and real life triage performance, respectively. Specificity results were similarly diverse ranging from 17.0% to 93.1% for theoretical accuracy and 46.3% to 78.9% for actual paramedic decisions. Most studies had unclear or high risk of bias and applicability concerns. There were no obvious differences between different triage tools, and findings did not appear to vary systematically with major trauma prevalence, age, alternative reference standards, study designs, or setting. CONCLUSION: Existing prehospital triage tools may not accurately identify elderly patients with serious injury. Future work should focus on more relevant reference standards, establishing the best trade-off between undertriage and overtriage, optimizing the role prehospital clinician judgment, and further developing geriatric specific triage variables and thresholds. LEVEL OF EVIDENCE: Systematic review, level III. Abstract : Supplemental digital content is available in the text.